Infliximab Versus Adalimumab in the Treatment of Refractory Inflammatory Uveitis: A Multicenter Study From the French Uveitis Network. Issue 6 (26th May 2016) - Vallet, Hélène; Seve, Pascal; Biard, Lucie; Baptiste Fraison, Jean; Bielefeld, Philip; Perard, Laurent; Bienvenu, Boris; Abad, Sébastien; Rigolet, Aude; Deroux, Alban; Sene, Damien; Perlat, Antoinette; et al.
Abstract : Objective: To analyze the factors associated with response to anti–tumor necrosis factor (anti‐TNF) treatment and compare the efficacy and safety of infliximab (IFX) and adalimumab (ADA) in patients with refractory noninfectious uveitis. Methods: This was a multicenter observational study of 160 patients (39% men and 61% women; median age 31 years [interquartile range 21–42]) with uveitis that had been refractory to other therapies, who were treated with anti‐TNF (IFX 5 mg/kg at weeks 0, 2, 6, and then every 5–6 weeks [n = 98] or ADA 40 mg every 2 weeks [n = 62]). Factors associated with complete response were assessed by multivariate analysis. Efficacy and safety of IFX versus ADA were compared using a propensity score approach with baseline characteristics taken into account. Subdistribution hazard ratios (SHRs) and 95% confidence intervals (95% CIs) were calculated. Results: The main etiologies of uveitis included Behçet's disease (BD) (36%), juvenile idiopathic arthritis (22%), spondyloarthropathy (10%), and sarcoidosis (6%). The overall response rate at 6 and 12 months was 87% (26% with complete response) and 93% (28% with complete response), respectively. The median time to complete response was 2 months. In multivariate analysis, BD and occurrence of >5 uveitis flares before anti‐TNF initiation were associated with complete response to anti‐TNF (SHR 2.52 [95% CI 1.35–4.71], P  = 0.004 and SHR 1.97 [95% CI 1.02–3.84], P  = 0.045, respectively). Side effects were reported in 28% of patients, including serious adverse events in 13%. IFX and ADA did not differ significantly in terms of occurrence of complete response (SHR 0.65 [95% CI 0.25–1.71], P  = 0.39), serious side effects (SHR 0.22 [95% CI 0.04–1.25], P  = 0.089), or event‐free survival (SHR 0.55 [95% CI 0.28–1.08], P  = 0.083). Conclusion: Anti‐TNF treatment is highly effective in refractory inflammatory uveitis. BD is associated with increased odds of response. IFX and ADA appear to be equivalent in terms of efficacy.